Playback delay in mesh-based Peer-to-Peer systems with random packet forwarding and transmission capacity limitations. (11th March 2009) - Fodor, Viktoria; Chatzidrossos, Ilias
In meshed-based peer-to-peer streaming systems peers forward packets to their neighbours based on local scheduling decisions. The local decisions affect how packets get distributed in the mesh and consequently the distribution of the transmission delays. We propose an analytic framework that allows the evaluation of various scheduling algorithms. Two solutions are considered where scheduling is performed at the forwarding peer. We evaluate the effectiveness of the solutions in terms of the probability that a peer can play out a packet vs. the playback delay, and the scalability of the solutions with respect to the size of the overlay. Finally we discuss the effects of limited download bandwidth on the data dissemination.